Analisis Kesiapan Guru IPA/Kimia Terhadap Penerapan Pembelajaran STEM (Science Technology, Engineering, Mathematics) di SMA/SMK/MA Negeri Se Kecamatan Gerung - Faiqotuzzahrok, Elok; Al Idrus, Syarifa Wahidah; Junaidi, Eka (FKIP University of Mataram, 2025)
This study aims to describe the readiness of science/chemistry teachers for the application of STEM learning (Science, Technology, Engineering, Mathematics) and to describe the supporting and inhibiting factors of science/chemistry teacher readiness for the application of STEM learning. This research is a descriptive research with a quantitative approach. The population of this study is the number of science/chemistry teachers who teach at SMA/SMK/MA Country in District Gerung. The sampling technique in this study used purposive sampling. The number of samples was 12 science/chemistry teachers in SMA/SMK/MA Country in District Gerung. Data collection techniques using interview guidelines and questionnaire techniques which have been declared valid and reliable. The results of the research on attitude readiness, emotional readiness, cognitive readiness and behavioral readiness in public SMA/SMK/MA Country in District showed an average gain of 74.04%. This means that the readiness of science/chemistry teachers towards the application of STEM learning is more likely to be ready. Based on this, it can be interpreted that some teachers have implemented STEM learning and have never implemented STEM learning, only to the extent that they are ready to do STEM learning. This readiness is also influenced by supporting factors such as: responsibility, enthusiasm, willingness to adapt, critical thinking, thinking contextually, aware of one's own worth and will, being able to integrate various scientific disciplines, carrying out partnership functions and being good at managing time. While the inhibiting factors are independence and awareness of strengths and weaknesses, this is because some teachers have never participated in STEM learning training and teachers have never tried to apply STEM education in science/chemistry learning. Furthermore, teachers find it difficult to improve their quality in preparation for implementing STEM learning and teachers are not yet proficient in preparing lesson plans that are appropriate to STEM learning.